Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone, novel cytokine modulators via sharpless asymmetric epoxidation and L-proline catalyzed mannich reaction - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron, 2006)
A short and efficient enantioselective synthesis of (-)-cytoxazone and its stereoisomer (+)-epi-cytoxazone, novel cytokine modulators, has been described with good yield and enantioselectivity. Ti-catalyzed Sharpless asymmetric epoxidation of allyl alcohol and L-proline catalyzed three-component Mannich reaction constitute the key steps in introducing stereogenicity into the molecule. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Asymmetric synthesis; epoxidation; Mannich reaction; Oxidation; Ozonolysis

Enantioselective synthesis of (S,S)-ethambutol using proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2006)
An efficient enantioselective synthesis of (S,S)-ethambutol, a tuberculostatic antibiotic, has been achieved in 99% ee via both proline-catalyzed alpha-aminooxylation and alpha-amination of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.

Efficient organocatalytic route to the atorvastatin side-chain - George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An organocatalytic route to the synthesis of the atorvastatin side-chain, a building block present in the statin family, is described using L-proline-catalyzed alpha-aminooxylation of an aldehyde. The method also employs an iodine-induced intramolecular electrophilic cyclization of a carbonate to produce the iodocarbonate in a highly diastereoselective manner. (C) 2007 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone via Rh-catalyzed diastereoselective oxidative C-H aminations - Narina, Srinivasarao V.; Kumar, Talluri Siva; George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An efficient enantioselective synthesis of (-)-cytoxazone (1) and (+)-epi-eytoxazone (2) using proline-catalyzed asymmetric alpha-amino-oxylation of aldehydes followed by Rh-catalyzed diastereoselective oxidative C-H amination as the key steps is described. syn or anti 1,2-aminoalcohols were obtained by Rh-catalyzed intramolecular amidation of the C-H bonds of carbamates or sulfamate esters with good to excellent diastereoselectivity. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (S)-timolol via kinetic resolution of terminal epoxides and dihydroxylation of allylamines - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (S)-timolol has been described using chiral Co-salen-catalyzed kinetic resolution of less expensive (+/-)-epichlorohydrin with 3-hydroxy-4-(N-morpholino)-1,2,5-thiadiazole in good overall yield (55%) and excellent enantioselectivity (98%). Synthesis of (S)-timolol has also been achieved using hydrolytic kinetic resolution as well as asymmetric dihydroxylation routes in 90% ee and 56% ee, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric reactions; diols; epoxides; Kinetic resolution; oxazolidinone

Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis

Enantioselective synthesis of HIV protease inhibitor amprenavir via Co-catalyzed HKR of 2-(1-azido-2-phenylethyl)oxirane - Gadakh, Sunita K.; Reddy, R. Santhosh; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A short and efficient enantioselective synthesis of the HIV protease inhibitor amprenavir 1 (99% ee) as well as a formal synthesis of saquinavir 3 have been achieved in high enantiomeric purity starting from commercially available materials. Our strategy mainly comprises a Co-catalyzed two-stereocentred hydrolytic kinetic resolution (HKR) of racemic 2-(1-azido-2-phenylethyl)oxirane as the chirality inducing step. Also presented is a concise synthesis of (S)-3-hydroxytetrahydrofuran 4, the key structural feature, in high enantiomeric purity (98% ee). (c) 2012 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of guggultetrol and D-ribo-phytosphingosine tetraacetate via L-proline catalyzed sequential alpha-aminooxylation/Horner-Wardsworth-Emmons olefination-Sharpless asymmetric dihydroxylation strategy - Venkataramasubramanian, V.; Kumar, B. Senthil; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient enantioselective synthesis of two bioactive molecules, that is, guggultetrol and D-ribo-phytosphingosine, is described with high enantioselectivity (>98% ee) starting from commercially available 1-hexadecanol. The synthesis comprises organocatalyzed sequential alpha-aminooxylation of an aldehyde followed by Horner-Wardsworth-Emmons olefination and Sharp less asymmetric dihydroxylation as the key chiral inducing steps. For both syntheses, gamma-hydroxy-alpha,beta-unsaturated ester serves as the common intermediate obtained from proline catalysis. (C) 2015 Elsevier Ltd. All rights reserved.